Virtual reality, real emotions: a novel analogue for the assessment of risk factors of post-traumatic stress disorder - Dibbets, Pauline; Schulte-Ostermann, Michel A. (Frontiers in Psychology, 2015)
Most people are exposed to a violent or life-threatening situation during their lives, but only a minority develops post-traumatic stress disorder (PTSD). Experimental studies are necessary to assess risk factors, such as imagery ability, for the development of PTSD. Up to now the trauma film paradigm has functioned as an analogue for PTSD. This paradigm is known to induce involuntary intrusions, a core symptom of PTSD. Though useful, the film paradigm has a drawback, the participant remains an ‘outsider’ and does not immerse in the film scenes. The aim of the present study was to develop a fitting virtual reality (VR) analogue for PTSD and to assess risk factors for the development of PTSD-symptoms, such as intrusions. To this end a novel VR paradigm was compared to the traditional trauma film paradigm (TFP). Both the VR and TFP elicited a negative mood and induction-related intrusions. More immersion was observed in the VR paradigm compared to the TFP. The results of the risk factors were mixed; more imagery ability coincided with a higher intrusion frequency, but also with less distressing intrusions. The results, implications and suggestions for future research are discussed.